Urbanization and Land use/Land Cover Change in Varanasi City - Prasad, Sant; Singh, R.B. (National Geographical Journal of India, 2022)
Urban areas contribute a significant share to nation’s gross domestic product (GDP). In India, the urban population is currently 31.16 per cent of the total population and it contributes over 60 per cent of India’s GDP. It is projected that urban India will contribute nearly 75 per cent of the national GDP in the next 15 years. Cities are also referred to as the engines of economic growth. There is an increasing need for the cities to get smarter to handle this large-scale urbanization and finding new ways to manage risk, increase efficiency, and improve quality of life. The present study of land cover of Varanasi City from 2001 to 2016 (15 years) shows rapid change in the landscape as there is high growth in the built up area only within fifteen years. The study is based on the detection of change in the urban land cover of Varanasi City using temporal data of Landsat TM 7 and Landsat ETM images of 2001 and 2016. Detection of change by using images of two decades is very much effective as it is projects the variation in the landscape over time. Evaluation of the urban landscape change from 2001 to 2016 can provide important information on decision making processes as it can indicate the increase in urban area or reduction in vegetated area, with significant impact on the environment. Built-up areas have occupied the sparse and densely vegetated lands while fallow land has reduced marginally and water body is showing almost stagnant condition over time